Improving the torsional response of asymmetric buildings with self-centering controlled rocking steel braced frame system - Hafezi, Maryam; Aziminejad, Armin; Mansoori, Mohammad Reza; Hosseini, Mahmood; Moghadam, Abdolreza Sarvghad (Sage Publications Inc, 2022)
Self-centering controlled rocking steel braced-frame (SC-CR-SBF) is proposed as an earthquake-resistant system with low damage. Pre-stressed vertical strands provide a self-centering mechanism in the system and energy absorbing fuses restrict maximum displacement. Presence of asymmetry in structures can highlight the advantages of employing this structural system. Moreover, these days designing and constructing asymmetric and irregular structures is inevitable and as a result of architectural attractiveness and requirements of different functions of buildings, they are of great importance. Consequently, in these types of structures in order to minimize seismic responses, particular measures should be taken into consideration. Proper distribution of strength and stiffness throughout the plan of structures with self-centering systems can play a considerable role in resolving problems associated with asymmetry in these structures. In this study, the asymmetric buildings with 10% and 20% mass eccentricities and having different arrangements of centers were simulated. The models were analyzed under a set of 22 bidirectional far-field ground-motion records and corresponding responses of maximum roof drift, acceleration and rotation of the roof diaphragms of the structures with different arrangements of the center of mass, stiffness and strength were computed and studied. Results show that proper distribution of stiffness and strength throughout the plan of the structures with SC-CR-SBF system reduces the maximum roof drift as well as the rotation of the roof diaphragm. With appropriate arrangement of the centers, maximum drift response of the asymmetric structure decreases as much as roughly 20% and the ratio of the maximum drift response of the asymmetric structure to the response of the similar symmetric structure with the same overall stiffness and strength was 1.1. In other words, maximum drift response of the asymmetric structure with SC-CR-SBF system is acceptably close to the one for the symmetric building.
Keywords: asymmetric building; mass eccentricity (e(m)); strength eccentricity (e(v)); self-centering controlled rocking steel braced-frame; maximum drift response ratio